Thaharah dalam Perspektif Al-Qur’an: Fondasi Kebersihan Jasmani dan Ruhani dalam Kehidupan Muslim - Alfin, Naela Nuril (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2022)
Thaharah, or purification, is a fundamental concept in Islamic teachings that functions as a prerequisite for valid worship and as a manifestation of physical and spiritual cleanliness. In practice, thaharah includes various methods of purification such as wudhu (ablution), tayammum (dry purification), ghusl (ritual bath), and istinja (cleansing after relieving oneself), each with specific conditions and procedures. This study aims to explain the types of thaharah, their implementation, and their relevance in daily life, from the perspectives of both religious observance and public health. The research adopts a qualitative approach using library research methods, relying on classical and contemporary Islamic legal sources. The findings highlight that a proper understanding of thaharah is essential in shaping a disciplined, clean, and Sharia-compliant Muslim identity. Thaharah has significant impacts not only on spiritual well-being but also on personal hygiene and environmental cleanliness. Therefore, education on thaharah should be introduced early in life as part of character building and the cultivation of an Islamic lifestyle.